Truth-telling in a priority pricing mechanism - Prakriti Thami (Lund University, School of Economics and Management, Department of Economics, 2025)
This paper studies the impact of truth-telling preferences on aggregate consumer welfare within a priority pricing (PP) mechanism. Traditional models assume individuals always misrepresent private information to maximize payoffs, yet recent evidence suggests there may be an innate preference for truth-telling. By incorporating these preferences into a theoretical framework, I show that PP enhances welfare over uniform pricing only when the probability of non-truthful individuals surpasses a critical threshold, suggesting that PP may benefit populations with low truth-telling tendencies but reduce welfare when this tendency is high. To empirically test this, I conducted an online experiment, finding that while PP incentivized truth-telling, its impact did not vary significantly across groups with differing truth-telling tendencies. Instead, participants' beliefs about others' truthfulness emerged as key in shaping behavior. These findings underscore that PP's welfare-enhancing potential depends not only on incentives created by the pricing structure but also on the population's truth-telling tendencies and beliefs, offering valuable insight for designing effective pricing mechanisms.
Keywords: D82; D9; D47; D61; 330; priority pricing; consumer welfare; truth-telling behavior; incentive-compatible pricing